Myoepithelial carcinoma or epithelioid sarcoma – A rare diagnosis with poor prognosis. A case report and review of literature. (2018) - Khazeni, Kristina; LaBove, Hannah; Wilky, Breelyn; Rosenberg, Andrew E.; Paulus, Elizabeth; Chim, Harvey; Pearson, Joseph M.; Yakoub, Danny
Highlights: Myoepithelial carcinoma of the vulva and epithelioid sarcoma has overlapping histological, immunohistochemical and genetic features. Similarities between two diagnoses in aggressive vulvar cancer should be noted as a sarcoma-based chemotherapy regimen should be considered. We recommend immediate surgical resection with bilateral superficial and deep inguinal lymph node dissections in these aggressive cancers. Identification of SMARCB1-deficiency trials of targeted therapies such as EZH2 inhibitors which show promise in halting further progression. Abstract: Introduction: Myoepithelial carcinoma and proximal-type epithelioid sarcoma of the vulva are two rare malignancies with known aggressive behavior. In addition to a similar clinical course, these two disease entities also have significant histologic and pathologic overlap. Given the rarity of these malignancies, there is limited literature on the appropriate treatment regimen. Nevertheless, there is a consensus that early surgical resection is beneficial in both cases. Presentation: We present a case of a patient who was initially diagnosed with myoepithelial carcinoma of the vulva with a differential later expanded to include possible epithelioid sarcoma. Discussion: We demonstrate the importance in early identification of a SMARCB1 deficiency. Additionally, we suggest an appropriate treatment regimen for these patients going forward. Specifically, we encourage consideration of bilateral superficial and deep inguinal lymphadenectomies. Furthermore, sarcoma based chemotherapy regimens in the appropriate clinical setting may be beneficial in treating SMARCB1 deficient tumors. Additionally, there are now clinical trials involving EZH2 Inhibitors which may offer benefit for similar patients going forward. Conclusion: This case highlights the difficulty in making a definitive diagnosis, and the importance in identifying a SMARCB1 deficiency as it will affect treatment options and may allow for enrollment in ongoing clinical trials.